Artificial Intelligence in Small and Medium Enterprises: A Quantitative Research in Southern Poland - Olga OKRZESIK; Jerzy DUDA (Communications of International Proceedings, 2024)
This study investigates AI adoption among Polish SMEs, addressing the gap in understanding AI readiness and perceptions in this crucial economic sector. With SMEs comprising 99% of Polish enterprises, their AI adoption is vital for economic competitiveness. The research employed a survey of 92 entrepreneurs in Southern Poland in late 2023 and early 2024. Key findings reveal a disparity between AI awareness and implementation: 69% of respondents are familiar with AI, but only 36% utilize AI technologies. Major barriers include limited financial resources, lack of expertise, and data security concerns. Despite challenges, SMEs recognize AI's potential benefits, particularly in marketing, customer management, and decision-making. The study highlights a significant gap between AI awareness and practical implementation in Polish SMEs. This underscores the need for targeted support, including hands-on training, expert consultations, and financial assistance to bridge this gap. The research contributes valuable insights into the current state of AI adoption in Polish SMEs, informing policymakers and stakeholders about the necessary steps to facilitate AI integration in this vital sector.
Keywords: Artificial Intelligence; Business management; Small and Medium-sized Enterprises; AI adoption